2020
DOI: 10.37789/ijusi.2020.13.1.4
|View full text |Cite
|
Sign up to set email alerts
|

NLP based Deep Learning Approach for Plagiarism Detection

Abstract: Plagiarism detection represents an application domain for the NLP research area, which has not been investigated too much by researchers in the context of lately developed attention mechanism and sentence transformers. In this paper, we present a plagiarism detection approach which uses state-of-the-art deep learning techniques in order to provide more accurate results than classical plagiarism detection techniques. This approach goes beyond classical word searching and matching, which is time-consuming and ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…In Ref. [13], the authors have compared the performances of Global Vectors for word representation(GloVe), Bidirectional Encoder Representations from Transformers(BERT) and Robustly Optimized BERT(RoBERTa) in detecting plagiarism in articles and have concluded that BERT has outperformed the other two methods. The authors of Ref.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In Ref. [13], the authors have compared the performances of Global Vectors for word representation(GloVe), Bidirectional Encoder Representations from Transformers(BERT) and Robustly Optimized BERT(RoBERTa) in detecting plagiarism in articles and have concluded that BERT has outperformed the other two methods. The authors of Ref.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Their work focuses on polarity, but research into assigning emotions to items stated in text is also a viable subject for future research. [15]. Sautera et al explored six emotions, which have been the subject of a lot of recent research.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Regarding scientific research articles it could be categorize plagiarism into (Kharat, Chavan, Jadhav, & Rakibe, 2013;Rosu, Stoica, Popescu, & Mihăescu, 2021): a) Using a source's keywords, words, sentences, facts, and/or information without citing the source in the citation notes or referencing the source appropriately. b) Referring to and/or randomly quoting keywords, words, sentences, data, and/or information from a source without citing the source and/or without completely identifying the source in the citation notes c) Citing a source for ideas, opinions, points of view, or hypotheses without properly citing the source.…”
mentioning
confidence: 99%